Pinning forces and defects as measured by critical currents in amorphous superconducting materials - Luzuriaga, J. (American Physical Society, 1987)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina